2008
DOI: 10.1007/s00531-008-0318-z
|View full text |Cite
|
Sign up to set email alerts
|

A late Holocene paleo-productivity record in the western Gulf of Maine, USA, inferred from growth histories of the long-lived ocean quahog (Arctica islandica)

Abstract: To investigate environmental variability during the late Holocene in the western Gulf of Maine, USA, we collected a 142-year-old living bivalve (Arctica islandica) in 2004, and three fossil A. islandica shells of the Medieval Warm Period (MWP) and late MWP / Little Ice Age (LIA) period (corrected 14 C AMS = 1030 ± 78 AD; 1320 ± 45 AD; 1357 ± 40 AD) in 1996. We compared the growth record of the modern shell with continuous plankton recorder (CPR) time-series from the Gulf of Maine. A significant correlation (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 53 publications
1
30
0
Order By: Relevance
“…However, the relative importance of the main factors, temperature and food supply/quality driving shell formation are still not well understood. Positive correlations between shell growth and water temperature have been identified (i.e., Schöne et al, 2005;Wanamaker et al, 2009;Marali et al, 2015), but the relationship between shell growth and environment is more complex (Marchitto et al, 2010;Stott et al, 2010; and likely dependent on the synergic effect of food availability and water temperature (Butler et al, 2013;Lohmann and Schöne, 2013;Mette et al, 2016). Tank experiments were run in order to precisely identify the role of these two parameters on the shell growth of A. islandica (Witbaard et al, 1997;Hiebenthal et al, 2012).…”
Section: Environmental Influence On Shell Growthmentioning
confidence: 99%
“…However, the relative importance of the main factors, temperature and food supply/quality driving shell formation are still not well understood. Positive correlations between shell growth and water temperature have been identified (i.e., Schöne et al, 2005;Wanamaker et al, 2009;Marali et al, 2015), but the relationship between shell growth and environment is more complex (Marchitto et al, 2010;Stott et al, 2010; and likely dependent on the synergic effect of food availability and water temperature (Butler et al, 2013;Lohmann and Schöne, 2013;Mette et al, 2016). Tank experiments were run in order to precisely identify the role of these two parameters on the shell growth of A. islandica (Witbaard et al, 1997;Hiebenthal et al, 2012).…”
Section: Environmental Influence On Shell Growthmentioning
confidence: 99%
“…First, we applied the Morlet wavelets (Morlet 1983; Torrence and Compo 1998), a continuous wavelet transform, proven and tested in climate time series analysis (Lau and Weng 1995;Dunca et al 2009;Schöne and Fiebig 2009;Wanamaker et al 2009). The transform was based on the method described in Torrence and Compo (1998) by means of Wavelet software provided by these authors.…”
Section: Statistical Evaluationmentioning
confidence: 99%
“…This would, however, be an essential step to unambiguously link our 5-year signal to the NAO (cf., Wunsch 1999). A number of studies have shown indeed A. islandica shell growth patterns to correlate with known ocean-atmosphere oscillations such as NAO (Schöne et al 2003a;Wanamaker et al 2009). Nevertheless, further investigations of additional shell material as well as of local forcing mechanisms are required.…”
Section: Discussionmentioning
confidence: 96%